Factors predicting the acquisition of soft skills among students with learning disabilities in vocational special education secondary school - Ab Halim, Fazlinda; Muhammad, Nurul Awanis; Wan Muda, Wan Hanim Nadrah (2024)
Acquiring soft skills is essential for all students, including those with disabilities, as these skills contribute to personal and professional success. Soft skills are non-technical abilities that enable individuals to work well with others, communicate effectively, and adapt to various situations. Students with disabilities may face unique challenges in developing their soft skills. This research determined the factors affecting the acquisition of soft skills among students with learning disabilities in Vocational Special Education Secondary Schools. Survey research design is a methodological approach used in this study to collect data from samples by administering a questionnaire. This study focuses on soft skills, which consist of seven elements (communication skills, critical thinking and problem-solving skills, teamwork skills, information management and lifelong learning skills, entrepreneurship skills, moral and ethics skills and leadership skills), self-esteem and self-efficacy as variables. Two secondary schools are involved in this study: Vocational Special Education Secondary School Shah Alam, Selangor and Vocational Special Education Secondary School Indahpura, Johor, with a total sample of 52 students. Data analysis revealed that the combination of variables to predict the acquisition of soft skills from self-esteem and self-efficacy was statistically significant. In conclusion, selfesteem and self-efficacy influence the acquisition of soft skills among students with learning disabilities in Vocational Special Education Secondary Schools.